A compact wideband microstrip antenna intergrated with band-notched design - Jalil Y.E.; Chakrabarty C.K.; Kasi B. (EuroJournals, Inc., 2023)
This article describes a compact ultra-wideband (UWB) antenna that shows desirable band-notch and gain characteristics. The proposed antenna consists of a rectangular patch with a truncated ground plane that is fed by a 50 ? microstrip line. A band-stop function to eliminate the WLAN interfering signals is created by inserting two C-shape slots on the proposed radiator. It is shown that the frequency of the band-notch characteristic can be tuned by varying the parameters of the notching structure. The predicted and measured results show that the antenna achieves good impedance matching and reasonable radiation patterns over a bandwidth of 3 to 8.2 GHz. Furthermore, the fabricated antenna has a compact size of 23 24 mm2 while exhibiting the band rejection performance in the frequency band of 4.8 to 5.8 GHz. 2012 EuroJournals Publishing, Inc.